FAKTOR – FAKTOR YANG MEMPENGARUHI AUDIT REPORT LAG PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR PADA BURSA EFEK INDONESIA TAHUN 2017 - 2022 - Muhammad Rafi Eldi Putra; Darsono Darsono (Diponegoro Journal of Accounting, 2023)
The aim of this study is to empirically examine the relationship between profitability, company size, operational complexity, independent commissioners, auditor industry specialization, and the Covid-19 pandemic on audit report lag from 2017 to 2022. The dependent variable used in this study is audit report lag, while the independent variables include profitability, company size, operational complexity, independent commissioners, auditor industry specialization, and the Covid-19 pandemic.This study utilizes secondary data with purposive sampling method to select banking company reports from 2017 to 2022 listed on the Indonesia Stock Exchange. The sample consists of 256 data points. The analysis method used is multiple linear regression. Classical assumption tests are conducted prior to conducting multiple regression analysis.The results of this study indicate that the independent variables, profitability, and company size have a significant negative influence on audit report lag. The Covid-19 pandemic variable has a significant positive influence on audit report lag. Operational complexity, independent commissioners, and auditor specialization variables do not have a significant influence on audit report lag.